(untitled) (Journal of Parents and Teachers, 2014)
The article deals with the importance of a good investment in education. In fact, the author analyzes the social reality of Spain, attending to social and political values and using them to justify his position. In this way, the author emphasizes the need for quality education and a system that educates in indispensable values such as love, solidarity and helping others.